Sengketa Maritim Di Kalimantan Barat: Dinamika Kesultanan, Kekuatan Eropa, Dan Aliansi Bajak Laut Tahun 1811-1850 - Baihaqi, Ahmad Fauzan; Bryna, Bryna Rizkinta S; Ramadhan, Fauzan Syahru; Panditra, Aditia Muara (PURBAWIDYA, 2025)
This article aims to investigate the roots of piracy on the west coast of Kalimantan during the 19th centuries, focusing on the complex interactions between the Pontianak and Sambas Sultanates and European powers. Challenging the common assumption that pirates in the region originated mainly from Sulu Mindanao and Bugis, this study employs a critical historical method to systematically analyze colonial sources and primary texts from the sultanates. The findings reveal that pirates on the west coast of Kalimantan were led by the Sultan and Prince Anom of the Sambas kingdom, who formed an alliance with the Ilanun to attack traders in Pontianak, Mempawah, and Banjar. Additionally, pirate activity was found around Sukadana Bay by the Tanjung Pura community due to the collapse of the Sukadana Kingdom's maritime power resulting from Dutch East Indies colonial expansion. The study highlights the complex interplay between political power dynamics and the challenges of piracy in the region, shedding light on sensitive issues in the collective memory of the local population. These findings contribute to a deeper understanding of Borneo's maritime history and the socio-political factors that shaped piracy during the colonial period, emphasizing the need for a new approach in studying the maritime world of the Indonesian archipelago, particularly the coastal areas of West Kalimantan.